2016
DOI: 10.1155/2016/4395063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rubberized Bitumen Blending Methods on Permanent Deformation of SMA Rubberized Asphalt Mixtures

Abstract: This study aims at comparing the permanent deformation of Stone Mastic Asphalt (SMA) rubberized asphalt mixtures produced by the wet process. In this study, rubberized binders were prepared using two different blending methods, namely, continuous blend and terminal blend. To study the creep behaviour of control and rubberized asphalt mixtures, the dynamic creep test was performed using Universal Materials Testing Apparatus (UMATTA) at different temperatures and stress levels. Zhou three-stage creep model was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Its physical properties and particle distribution were listed in Tables 6 and 7. [45,46]. In this research, SMA-13 gradation was designed based on the Course Aggregate Void Filling (CAVF) method [47].…”
Section: Raw Materialsmentioning
confidence: 99%
“…Its physical properties and particle distribution were listed in Tables 6 and 7. [45,46]. In this research, SMA-13 gradation was designed based on the Course Aggregate Void Filling (CAVF) method [47].…”
Section: Raw Materialsmentioning
confidence: 99%
“…Decline of creep deformation is mainly caused by the following reasons. Firstly, Katman et al [54] had indicated that the stress level affected its viscoelastic deformation significantly. Mortar stress moves to the low level under the bridging action of fibers.…”
Section: Creep Deformationmentioning
confidence: 99%
“…The CRMA was widely used due to its excellent performance and efficient preparation process. The incorporation of CR into asphalt was reported to be able to enhance the comprehensive performance of asphalt pavement in terms of traffic noise reduction, driving safety improvement, high and low-temperature performance promotion, fatigue resistance and water stability (Katman et al ., 2016; Yu et al ., 2020; Roychand et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%